DPP-4 inhibition ameliorates atherosclerosis by priming monocytes into M2 macrophages. (15th November 2015) - Brenner, C.; Franz, W.M.; Kühlenthal, S.; Kuschnerus, K.; Remm, F.; Gross, L.; Theiss, H.D.; Landmesser, U.; Kränkel, N.
Abstract: Objective: Glipitins are widely used for the treatment of type 2 diabetic patients. In addition to their improvement of glycemic control, animal studies have suggested an independent anti-atherosclerotic effect of gliptins. Nevertheless, recent clinical trials regarding long-term effects of gliptin therapy on vascular events have been disappointing. This discrepancy led us to better dissect the functional role of SDF-1/CXCR4 signaling as a potential mechanism underlying gliptin action. The study should give improved understanding of the potential of gliptin therapy in the prevention and treatment of atherosclerosis. Methods and results: In an ApoE −/− mouse model on high cholesterol diet, long-term treatment with the DPP-4 inhibitor Sitagliptin significantly reduced atherosclerosic plaque load in the aorta. Flow cytometry analyses showed an enrichment of M2 macrophages in the aortic wall under gliptin therapy. Importantly, the number of recruited CD206 + macrophages was inversely correlated with total plaque area while no correlation was found for the overall macrophage population or M1 macrophages. Blockade of CXCR4/SDF-1 signaling by AMD3100 inhibited aortic M2 accumulation and the therapeutic effect of Sitagliptin. Correspondingly, Sitagliptin shifted the polarization profile of macrophages towards a M2-like phenotype. Conclusion: Sitagliptin-mediated inhibition of early atherosclerosis is based on M2-polarization during monocyte differentiation via the SDF-1/CXCR4 signaling. In contrast to earlier assumptions gliptin treatment might be especially effective in prevention of atherosclerosis.